Northwind - Paulsen, Gary 1939-2021 (Farrar Straus Giroux, 2022)
When sickness decimates his fishing camp, an orphan named Leif flees north in a cedar canoe, journeying along a brutal but beautiful coastline
Keywords: Wilderness survival / Juvenile fiction; Survival / Juvenile fiction; Orphans / Juvenile fiction; Diseases / Juvenile fiction; Canoes and canoeing / Juvenile fiction; Wilderness survival / Fiction; Survival / Fiction; Orphans / Fiction; Survie en milieu sauvage / Romans, nouvelles, etc. pour la jeunesse; Habiletés de survie / Romans, nouvelles, etc. pour la jeunesse; Maladies / Romans, nouvelles, etc. pour la jeunesse; JUVENILE FICTION / Action & Adventure / Survival Stories; JUVENILE FICTION / Historical / Europe; JUVENILE FICTION / Science & Nature / General; Canoes and canoeing; Diseases; Orphans; Survival; Wilderness survival; Survival after airplane accidents, shipwrecks, etc / Juvenile fiction; Adventure fiction; Survival after airplane accidents, shipwrecks, etc / Fiction; Adventure and adventurers / Fiction; Fictional Work; Novels; Action and adventure fiction; Fiction; Juvenile works; Romans; Jugendbuch